Emersive VR: An expanded immersive VR practice. Issue 2 (1st October 2021) - Chang, Haoran
Creating an immersive isolated virtual environment is the canon in the current mainstream virtual reality (VR) practice and design. Audiences are usually situated in a singular and complete form of space in VR to receive the fully immersive experience. Nevertheless, in this article, I propose a different way of thinking about the practice and design of VR. Rather than seeing VR as a singular and isolated space in relation to other spaces, I am considering a potentiality to have a more expansive and reflexive VR practice and design. I call this emersive VR in contrast to immersive VR. Emersion is a concept borrowing from body ecology, which is a field based on the philosophy of awakening and consciousness. Emersion in body ecology is different from immersion in that people can still sustain self-consciousness without being subsumed by the other. In the notion of emersive VR, audiences are not located in a singular and complete virtual space but in a differential space between the physical and the virtual. The spatial difference is folded through the VR experience perceived by the audiences. In this article, I highlight two different approaches to construct an emersive VR experience: expanded sensory VR and reflexive storytelling. In both, audiences are not isolated in a singular virtual world but in a differential space with multiple embodiments. Emersive VR is a reconfiguration of immersive VR. It is to expand the idea of immersive VR and sketch a more dynamic future of VR as a critical medium.